Analisis Struktur Naratif dalam Teks Rukmini Tattwa - I Made Gami Sandi Untara (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2021)
The text of Rukmini Tatwa is a papyrus text that uses plant diversity to maintain body fitness. Rukmini Tatwa is a text that reviews women's beauty care in the Rukmini Tatwa text there is a text structure consisting of: 1) The incident contained in the Rukmini Tatwa text is when a conversation occurs between Rukmini and Bhatari Saci about how to take care of self beauty for women in the existence of its gender as a male companion as the wife of the husband, 2) The plot, the Rukmini Tatwa text is good because the cause-and-effect relationship is very clear in the formation of the story in the Rukmini Tatwa text, 3) The theme contained in the Rukmini Tatwa text is the theme of personal beauty care for women in their gender existence as male companions as wives of husbands. This can be seen in a short dialogue between Dewi Rukmini and Bhatari Saci, 4) Characterizations The main characters in the Rukmini Tatwa text are Dewi Rukmini and Bhatari Saci. Dewi Rukmini is one of the wives of Sri Kresna while Bhatari Saci is the wife of Dewa Indra, and 5) The mandate contained in the Rukmini Tatwa text can be seen when seeing Rukmini's efforts to bring Dewi Saci magically (ngredana) aimed at asking for knowledge that is very With the hope that after learning Dewi Saci's knowledge, Rukmini will be able to maintain the integrity of Krsna's love, so that the other wives no longer pose a serious threat to her existence in the eyes of Krishna. Thanks to her diligent efforts, finally Rukmini succeeded in lowering Dewi Saci from heaven and at the same time getting the secret of her greatness.Keywords: Care, Beauty, Rukmini Tatwa